Benzoxazolinone aryl sulfonamides as potent, selective Nav1.7 inhibitors with in vivo efficacy in a preclinical pain model. Issue 12 (15th June 2017) - Pero, Joseph E.; Rossi, Michael A.; Lehman, Hannah D.G.F.; Kelly, Michael J.; Mulhearn, James J.; Wolkenberg, Scott E.; Cato, Matthew J.; Clements, Michelle K.; Daley, Christopher J.; Filzen, Tracey; Finger, Eleftheria N.; Gregan, Yun; et al.
Graphical abstract: Abstract: Studies on human genetics have suggested that inhibitors of the Nav 1.7 voltage-gated sodium channel hold considerable promise as therapies for the treatment of chronic pain syndromes. Herein, we report novel, peripherally-restricted benzoxazolinone aryl sulfonamides as potent Nav 1.7 inhibitors with excellent selectivity against the Nav 1.5 isoform, which is expressed in the heart muscle. Elaboration of initial lead compound3d afforded exemplar13, which featured attractive physicochemical properties, outstanding lipophilic ligand efficiency and pharmacological selectivity against Nav 1.5 exceeding 1000-fold. Key structure-activity relationships associated with oral bioavailability were leveraged to discover compound17, which exhibited a comparable potency/selectivity profile as well as full efficacy following oral administration in a preclinical model indicative of antinociceptive behavior.